Optimalisasi Strategi Segmentation, Targeting And Positioning dalam Meingkatkan Keunggulan Bersaing pada Franchise Teh Poci - Bella Mega Riswanti; Rusdi Hidayat Nugroho (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Teh Poci Franchise is growing to meet the demand of the community. To date, thousands of franchise brands and thousands of stores have spread throughout Indonesia. Pot Tea Franchise entrepreneurs must continue to innovate and improve shortcomings so that customers do not switch to other products because many rivals appear over time. Based on the results of this study, it is found that (1) Geographic segmentation, in its marketing, the products offered are not only spread in the UPN Veteran East Java area but spread in the East Surabaya area as a potential area in targeting the target market to meet consumer wants and needs. (2) Age 15 - 60 years targeting students who need a refreshing cold drink for activities on campus. (3) Teh Poci positions itself compared to other competitors in terms of taste quality and affordable prices. (4) The existence of several dominant teapot franchises around the UPN Veteran East Java campus can show that the teapot franchise is still superior to several existing competitors.